Predictor variables of performance in recreational male long-distance inline skaters - Knechtle, B.; Knechtle, P.; Rüst, C. A.; Senn, O.; Rosemann, T.; Lepers, R. (Journal of Sports Sciences, 2011)
We investigated the associations between selected anthropometric and training characteristics with race time in 84 recreational male long-distance inline skaters at the longest inline marathon in Europe, the `Inline One-eleven` over 111 km in Switzerland, using bi- and multivariate analysis. The mean (s) race time was 264 (41) min. The bivariate analysis showed that age (r = 0.30), body mass (r = 0.42), body mass index (r = 0.35), circumference of upper arm (r = 0.32), circumference of thigh (r = 0.29), circumference of calf (r = 0.38), skin-fold of thigh (r = 0.22), skin-fold of calf (r = 0.27), the sum of skin-folds (r = 0.43), percent body fat (r = 0.45), duration per training unit in inline skating (r = 0.33), and speed during training (r = -0.46) were significantly and positively correlated to race time. Stepwise multiple regression showed that duration per training unit (P = 0.003), age (P = 0.029) and percent body fat (P = 0.016) were the best correlated with race time. Race time in a long-distance inline race such as the `Inline One-eleven` over 111 km with a mean race time of 260 min might be predicted by the following equation (r 2 = 0.41):